Annual world Bank Conference on development Economics 2003 : [proceedings] : The new reform agenda - World Bank Annual Conference on Development Economics Washington, D.C. 2003; Pleskovic, Boris; Stern, Nicholas (Washington,D.C World Bank, 2003)
.
Introduction / Boris Pleskovic and Nicholas Stern -- Trade and poverty: Trade, growth, and poverty--A selective survey / Andrew Berg and Anne Krueger -- Doha and the poverty targets / L. Alan Winters -- Africa’s future: industrial or agricultural development: Primary commodity dependence and Africa’s future / Paul Collier -- Could Africa be like America? / Adrian Wood -- Education and empowerment: Education, empowerment, and gender inequalities / Ravi Kanbur -- Investment climate and productivity: Foreign direct investment to Africa: the role of price stability and currency instability / Carmen M. Reinhart and Kenneth S. Rogoff -- Appropriate institutions / Simeon Djankov, Rafael La Porta, Florencio Lopez-De-Silanes, and Andrei Shleifer -- Institutions matter / Daniel Kaufmann
Beginning with 2003 issue conference year precedes issue year. The conferences emphasize the contribution that empirical and basic economic research can make to understanding development process and to formulating sound development policies
Includes bibligraphies
Keywords: Economic development; ECONOMIC DEVELOPMENT; DEVELOPMENT POLICY; ECONOMIC RESEARCH; DEVELOPING COUNTRIES; CONFERENCES